The Influence of the Type of Surgical Thread and Suture in the Open Carpal Tunnel Syndrome Surgery - Marcelo José Silva Magalhães; Beatriz Xavier Cruz; Fabrício Conceição dos Santos; Isabella Mendes de Oliveira; João Pedro Saraiva Sousa; Thaís de Oliveira Guimarães; Thiago Antunes Lopes; Ernesto José Hoffmann (Brazilian Neurosurgery, 2017)
Carpal tunnel syndrome (CTS) is the result of compression and/or traction of the median nerve in the carpal tunnel. It is the most frequent compressive neuropathy of the upper limbs and it is usually idiopathic. Diagnosis is essentially clinical, defined by symptoms and provocative tests. Decompression of the median nerve by section of the transverse carpus ligament is the treatment of choice, but the lack of consensus on the type of suture and surgical thread to be used in the open carpal tunnel decompression surgery justifies the importance of evaluating the comparative results of existing studies, aiming to describe the influence of different types of sutures and surgical threads to guide the professionals about the most appropriate conduct. This is a systematic review of the international and national literature. Four studies comparing the influence of surgical threads and one study evaluating the influence of the type of suture were found. From the comparative studies, it was observed that there is advantage in the use of nonabsorbable suture due to the lower occurrence of inflammation and postoperative wound complications. When using Donatti sutures, wound edge inversion is less likely to occur compared with single individual sutures, but they are also related to longer postoperative pain.